Science communication on TikTok: toward transformative and post-normal science - Frick, Claudia; Grommes, Eva-Maria; Watanabe, Alice (Frontiers in Communication, 2025)
Science communication on social media is becoming increasingly important in order to promote an open dialog between science and the public. This raises the question of how to present topics related to climate change in a way that is both scientific and tailored to a non-specialist audience. The article takes up this question through the lenses of transformative and post-normal science using the TikTok channel @energiewende.erklaert run by Dr. Eva-Maria Grommes as an example. The case study illustrates how an individual researcher approaches science communication in an interactive way and demonstrates how scientific findings on the energy transition are communicated based on the needs expressed by those interacting with the researcher's content. @energiewende.erklaert effectively introduces scientific results into public discourse while maintaining scientific integrity and promoting inclusivity. Therefore, @energiewende.erklaert and TikTok act as a platform for scientists to experiment with interactive science communication. Dr. Eva-Maria Grommes acts as a representative of transformative science by stimulating debates outside the scientific system. At the same time, the content of @energiewende.erklaert is subject to post-normal conditions and thus allows conclusions to be drawn about lived practices, norms and roles. Ultimately, this highlights competences that researchers need beyond tailoring scientific findings to a non-specialist audience.